Proton loading of jets and other consequences of the injection of neutrons in accretion flows - Vila, Gabriela Soledad (2014)
Relativistic neutrons are injected in the corona surrounding an accreting black hole through hadronic interactions of locally accelerated protons. If the source is a microquasar, a fraction of these neutrons may escape and penetrate the base of the jet. The neutrons will decay into protons inside the outflow, this being then a possible mechanism for loading Poynting-dominated jets with baryons. We study the characteristics of the proton distribution injected in this way and the consequences on the high-energy radiative spectrum of the jet. We also investigate the fate of those neutrons that escape the corona into the external medium.